Uma análise da relação entre indicadores de gestão e a execução orçamentária das Universidades Federais do Nordeste - Carneiro, Rógera Paula Almeida (2017)
Considering the importance of public policy on higher education, the present study examined whether changes in total expenditure committed Federal universities (UF) of the Northeast can be explained by primary and indicators of performance established by the Tribunal de Contas da União. The expenditure committed total data of UF in the Northeast were generated through the SIOP and the explanatory variables, based on the management indicators, were collected in the management reports of each University. The data have been consolidated in a Panel for the period from 2012 to 2015, allowing the use of econometric techniques of panel data. Estimates were carried out in two specifications for different sets of explanatory variables, according to the model of stacked data, Fixed Effect model and Random Effect model. The results conclude that in both estimates not all management indicators explained the variations that occur in expenses, but stood out, for your statistical significance, the current cost/student equivalent, the degree of participation and the concept of CAPES for postgraduate courses.